Translation and the book trade in early modern Europe - Pérez Fernández, José María, 1963-; Wilson-Lee, Edward (Cambridge University Press, 2014)
"This volume provides the first transnational overview of the relationship between translation and the book trade in early modern Europe. Following an introduction to the theories and practices of translation in early modern Europe, and to the role played by translated books in driving and defining the trade in printed books, each chapter focuses on a different aspect of translated-book history - language learning, audience, printing, marketing, and censorship - across several national traditions. This study touches on a wide range of early modern figures who played myriad roles in the book world; many of them also performed these roles in different countries and languages. Topics treated include printers' sensitivity to audience demand; paratextual and typographical techniques for manipulating perception of translated texts; theories of readership that travelled across borders; and the complex interactions between foreign-language teachers, teaching manuals, immigration, diplomacy, and exile"--